The Discipline of Happiness: The Foucauldian Use of the “Positive Energy” Discourse in China’s Ideological Works - Chen, Zifeng; Wang, Clyde Yicheng (Journal of current Chinese affairs, 2019)
One important question about ideological works in China concerns the tension between mobilisation (encouraging public expression) and control (limiting public expression). Recently Xi Jinping’s administration has doubled down on both strategies. To study the rationale of this seemingly self-contradictory move, the authors examine the recently prominent ideological discourse of “positive energy.” Through a combination of online ethnography and discourse analysis using Foucauldian methods, we find that the discourse borrows and evolves from previous ideological works, but most importantly and distinguishably features a more dispersive, rather than centralised power structure. It penetrates popular culture and private lives, and by doing so disciplines people’s subjectivities, rather than only aiming at top-down persuasion or control. The logic of “positive energy” produces self-disciplined docile subjects, and quietly resolves the tension between mobilisation and control by having subjects internalise the interests of the state as their own good.